Iterative Meditations: The use of audio feature extraction tools on acousmatic composition - Oliveira Neto, Aluizio (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
This piece explores some possibilities of using Music Information Retrieval and Signal Processing techniques to extract acoustic features from recorded material and use this data to inform the decision making process that is intrinsic to music composition. By trying to identify or create sound descriptors that correlate to the composer’s subjective sensations of listening it was possible to compare and manipulate samples on the basis of this information, bridging the gap between the imagined acoustic targets and the actions required to achieve it. “Iterative Meditations” was created through an iterative process of listening, analyzing, acting and refining the analysis techniques used, having as end product the musical piece itself as well as gathering a collection of tools for writing music.